PENGARUH PENGUNGKAPAN INTELLECTUAL CAPITAL PROSPEKTUS TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL LAPORAN TAHUNAN PERUSAHAAN PUBLIK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2011 - Wulan Budi Astuti; Imam Ghozali (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of IC disclosure in the prospectus toward the disclosure of IC in annual reports issued by the company after IPO, as well as examine whether firms report IC information in the prospectus more than the annual report. This study investigated the prospectuses and annual reports of 43 companies that conduct initial listing on the Indonesia Stock Exchange since the year 2008-2011. IC disclosure investigated using the method of content analysis. Data processing method using a multiple linear regression. The results show that IC disclosure in the prospectus effect on IC disclosure in the annual report, as well as companies tend to disclose more IC information in the prospectus than in the annual report.